2016
DOI: 10.1007/s00253-015-7234-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites from nematophagous fungi and nematicidal natural products from fungi as alternatives for biological control. Part II: metabolites from nematophagous basidiomycetes and non-nematophagous fungi

Abstract: In this second section of a two-part mini-review article, we introduce 101 further nematicidal and non-nematicidal secondary metabolites biosynthesized by nematophagous basidiomycetes or non-nematophagous ascomycetes and basidiomycetes. Several of these compounds have promising nematicidal activity and deserve further and more detailed analysis. Thermolides A and B, omphalotins, ophiobolins, bursaphelocides A and B, illinitone A, pseudohalonectrins A and B, dichomitin B, and caryopsomycins A–C are excellent ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 72 publications
0
30
0
3
Order By: Relevance
“…There are few investments in the discovery of new drugs for the treatment of parasites. Considering that there are works in the literature relating nemathophagous fungi extracts with nematicidal activity and commercial products using nemathophagous fungi [7,18,19], we performed extraction of the P. chlamydosporia metabolites with an organic solvent; the extract was fractionated with solvents of different polarity scale and evaluated the compounds for nematicidal capacity. We observed that EtOAc was able to paralyze 84% of the C. elegans larvae at a concentration of 1,000 μg/mL, whereas CH 2 Cl 2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few investments in the discovery of new drugs for the treatment of parasites. Considering that there are works in the literature relating nemathophagous fungi extracts with nematicidal activity and commercial products using nemathophagous fungi [7,18,19], we performed extraction of the P. chlamydosporia metabolites with an organic solvent; the extract was fractionated with solvents of different polarity scale and evaluated the compounds for nematicidal capacity. We observed that EtOAc was able to paralyze 84% of the C. elegans larvae at a concentration of 1,000 μg/mL, whereas CH 2 Cl 2…”
Section: Discussionmentioning
confidence: 99%
“…The administration of nematophagous fungi is considered a promising alternative in the prophylaxis of parasitic gastrointestinal helminthiasis [5]. Willcox and Tribe [6] reported the association between the fungus Pochonia chlamydosporia and the nematode Heterodera schachtii, as the primary and secondary metabolites of nematophagous fungi have been known to be involved in this interaction [5,7,8]. In the review presented by Li et al [9], 179 substances from fungi, including nematophagous, were reported as potential nematicidal drugs; therefore, these fungi can be considered an important source of new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in cattle, efficacy was impaired when high FEC coincided with dung pat degradation due to rainfall (Dimander, Höglund, Uggla, Spörndly, & Waller, ). Metabolites and other natural products from fungi may also serve as biological control agents, and, for example, substances of the oligosporon type have shown some in vitro activity against H. contortus (Degenkolb & Vilcinskas, ). However, several of these compounds are unstable in pure form, and at present, they have not been explored for use in livestock.…”
Section: Main Means Of Detection Prevention and Controlmentioning
confidence: 99%
“…Some of these include: the antimalarial properties of Cordyceps species 2 and Bulgaria inquinans, 3 and the amoebicidal 4 and anti-trypanosomiasis 5 properties of Pleurotus ostreatus. Other reported biological activities include nematicidal, 6 anti-inflammatory and immunomodulatory, 7 and anticancer 8,9 properties among others. As a follow up to earlier reports on the scientific validation of the health benefits and the characterization of bioactive secondary metabolites from indigenous edible mushrooms in Nigeria, [10][11][12][13] the present study aimed to determine the nutraceutical potentials of the n-hexane extract (NHE) of the fruiting bodies of the edible mushroom P. ostreatus in the management of malaria infections.…”
Section: Introductionmentioning
confidence: 99%